Implementasi Pelaksanaan Pendidikan Inklusi di SDN Karawaci 5 Kota Tangerang - Nurfadhillah, Septy; Farlidya, Tasya; Saputra, Tio (Lembaga Yasin AlSys, 2022)
The purpose of this study is to find out how the implementation of the implementation of inclusive education in SDN KARAWACI 5 Tangerang City is. The method used in this study is a qualitative method, with the research subjects being individuals who participate in the research. Data analysis techniques used are data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that inclusive education services at SDN KARAWACI 5 have been maximized, this is because SDN KARAWACI 5 is an inclusive school based on the Appointment Decree appointed by the mayor. And the curriculum used at SDN KARAWACI 5 still uses the same one so that the needs and handling of ABK students are well accommodated. Meanwhile, the condition of teachers has not been supported by adequate teacher quality, because the management of education personnel is carried out according to regular standards and the limitations of regular teachers with understanding of ABK students. The facilities and infrastructure at SDN KARAWACI 5 do not meet the standards of sarpras, this is because there is no allocation of funds for the provision of sarpras for students with special needs. As well as special services at SDN KARAWACI 5 in special cases such as providing special services or special treatment for ABK students by holding additional classes every Friday and Saturday.